Brand Personality: Antecedents and Consequences - Merabet, Amina; Benhabib, Abderrezzak (Indian Journal of Marketing, 2012)
The understanding of branding, advertising, processing and buying decision making is necessary for the definition of consumer oriented branding strategy. Thus, the main purpose of this paper is to study the impact of persuasive advertising on the perception of brand personality. In the present study, the researchers have tried to determine the level of alteration features of brand personality as well as the attitudes toward brands and purchase intention in the case of either two types of processing that relates to central and peripheral persuasive advertising, and have tried to emphasize the moderating role of product involvement. The results validate the hypothesis that persuasive advertising has a significant impact on the personality traits formation of the brand. However, it shows a variation of influence depending on the treatment of persuasive advertising and product type.